SIMILARITIES AND DIFFERENCES BETWEEN ENGLISH AND ARABIC VERB - Siswoyo, Siswoyo (STKIP Muhammadiyah Pringsewu, 2016)
This paper is to know the similarities and differences between English and Arabic verb.The similarities between English and Arabic verb can be used as media to learn bothlanguages. The English verb is the same as Arabic that needs object and has theagreement of the subject and the verb. The difference between English and Arabic verbis that English verb has no change of the first letter of the verb because of the change ofthe various subject.Keywords: fiâil madli, mudloriâ, amr, transitive verb, intransitive verb